Impact of Trust, Service Quality, Price on Customer Satisfaction on E-Commerce Users Attitudes - Alfin Nurfadhilah Ramli; Ahmad Jidan Abrar; Dr. Osly Usman, M.Bus Syst (Journal of Strategic Marketing and Innovation, 2025)
E-commerce is a rapidly growing sector influenced by factors such as customer trust, service quality, pricing, and satisfaction. Customer trust and service quality impact satisfaction, while pricing influences purchasing decisions. Understanding these relationships is crucial for E-commerce platforms to enhance customer satisfaction and loyalty, facilitating long-term business growth. This research employed a quantitative method involving a questionnaire survey as the primary data collection tool. The questionnaire was utilized to gain insights and in-depth responses from the respondents regarding the research topic. The researcher chose to apply the Partial Least Square (PLS) method for data analysis. In conclusion, this research finds that trust positively impacts customer satisfaction and attitude. Service quality does not negatively affect satisfaction and has a positive effect on attitude. Price positively affects satisfaction but does not negatively impact attitude. Customer satisfaction positively influences customer attitude in using e-commerce, providing insights into e-commerce customer behaviour. Researcher recommends that other researchers exploring the same topic conduct studies in various fields of activity. Research in different domains will complement this study and enable more comprehensive decision-making on a global scale.